2014
DOI: 10.1155/2014/213745
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Immunoassay-Based Algorithm for Screening and Identification ofGiardiaandCryptosporidiumAntigens in Human Faecal Specimens from Saudi Arabia

Abstract: An immunoassay-based algorithm, involving three commercial kits, was introduced and evaluated for screening and identification of Giardia/Cryptosporidium antigens in human stool specimens. Initially, Giardia/Cryptosporidium Chek kit (TechLab), an enzyme-linked immunosorbent assay (ELISA), was adopted for screening. The ELISA-positive reactions were subsequently characterised by RIDA Quick Giardia and RIDA Quick Cryptosporidium immunochromatographic kits (R-Biopharm). A gold standard test comprising PCR and mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Giardia was detected in 27 patients, with an estimated prevalence rate of 16.5%. In the same setting, a prevalence of 8.5–15% has been reported in 2 earlier studies [ 26 , 27 ]. Cryptosporidium infection was identified with an estimated prevalence of about 9%, minimally lower than an estimate, about 10%, described in an earlier study based on an in-house PCR [ 13 ].…”
Section: Discussionsupporting
confidence: 64%
“…Giardia was detected in 27 patients, with an estimated prevalence rate of 16.5%. In the same setting, a prevalence of 8.5–15% has been reported in 2 earlier studies [ 26 , 27 ]. Cryptosporidium infection was identified with an estimated prevalence of about 9%, minimally lower than an estimate, about 10%, described in an earlier study based on an in-house PCR [ 13 ].…”
Section: Discussionsupporting
confidence: 64%
“…In the first case, the oocyst antigens shed in the absence of intact oocysts in feces, while in the second case, the oocysts shed in feces in a number below the detection limit of microscopy. In a previous work [ 25 ], we reported a sensitivity of 95% for the same kit but as part of a 3 kits-based screening algorithm. Also, a lower sensitivity of the same kit was displayed in a previous study [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Salman (2014) found that direct fluorescent assay and modified Ziehl-Neelsen methods show high sensitivity and specificity in Cryptosporidium diagnosis than ELISA-corpo antigen. On the other hand, Hawash (2014) recommended this test as rapid and highly sensitive and specific test.…”
Section: Discussionmentioning
confidence: 99%